Implementasi Model Pembelajaran Teaching Factory pada Program Keahlian Agribisnis Tanaman Pangan dan Hortikultura di SMKN 7 Ende - Wilfridus Kado; Ahmad Suryadi (Lembaga Yasin AlSys, 2026)
The implementation of Teaching Factory in vocational education continues to develop as a strategy to bring the learning process closer to the world of work, but studies that specifically discuss its application in the Program Keahlian Agribisnis Tanaman Pangan dan Hortikultura at SMKN 7 Ende remain limited. This study aims to analyze the implementation of Teaching Factory, the synchronization of the curriculum with industry needs, the application of a block-system learning schedule, as well as its supporting and inhibiting factors. This study employed a qualitative approach with a case study design. The research participants consisted of the principal, the vice principal for curriculum affairs, the head of the expertise program, productive teachers, the Teaching Factory coordinator, and students selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the Miles and Huberman model. The results showed that the implementation of Teaching Factory had been carried out through the use of the school’s practice land, but it did not yet fully reflect the industrial work system. Curriculum synchronization with industry needs was also not yet optimal, and the learning schedule had not implemented a block system for practice. The main supporting factors included the availability of land, the support of the principal, the agrarian condition of the region, and students’ enthusiasm, while the inhibiting factors included limited industry partnerships, teacher competence, production facilities, and the absence of an established school production unit. These findings emphasize the importance of developing a Teaching Factory based on local potential in a more systematic and sustainable manner in order to strengthen the linkage between vocational education and industry needs.